Boosting the lattice oxygen activity of Fe-catalyst for producing 2, 5-diformylfuran from 5-hydroxymethylfurfural. (15th January 2022) - Jia, Wenlong; Liu, Huai; Zhao, Xiaoyu; Feng, Yunchao; Zuo, Miao; Sun, Yong; Tang, Xing; Yang, Shuliang; Zeng, Xianhai; Lin, Lu
Graphical abstract: An efficiently synthesis of 2, 5-Diformylfuran from 5-hydroxymethylfurfural with FeCu@CN Highlight: The yield and purity of DFF was over 91% from fructose by two-step. The Cu and urea increased the Fe valence and activity of lattice oxygen. The redox cycle of Fe 3+ /Fe 2+ and Cu 2+ /Cu + played a crucial role in the oxidation. The oxygen transfer of oxidation was realized through the Mars-van Krevelen cycle. The vertical adsorption interaction guaranteed highly selective alcohols oxidation. Abstract: In this work, a novel bimetallic catalyst FeCu@CN was built by calcination of a Fe-Cu/cellulosic polymer framework precursor, which can be observed as FeCuOx nanoparticles well distributed on biochar. The as-synthesized FeCu@CN showed outstanding catalytic performance for producing 2, 5-diformylfuran (DFF) via selective oxidation of 5-hydroxymethylfurfural (HMF), which showed better performance compared to Fe-based catalysts once reported. With high TOF of 19.62 h 1 for the formation of DFF by using FeCu@CN, 98% of HMF conversion and 95% yield of DFF were effectively obtained using O2 as the oxidant in acetonitrile. The results and catalyst characterization revealed that the Cu sites and urea modification significantly increased the Fe valence and improved activity of lattice oxygen in the parallelogram carbon frame, thereby reducing the electronic transfer energy to preference Fe-HMF interaction. In this oxidative process, Fe 3+ played a pivotal catalytic performace by the redox cycle of Fe 2+ and Fe 3+, while Cu acted as a co-catalyst to facilitate it by the redox cycle of Cu 2+ and Cu + with Mars-van Krevelen oxidation mechanism.